A biografia de uma professora transexual em Brasilândia/MS: diálogos formativos e percursos sobre a diversidade sexual - Hélida Rodrigues de Lima (2021)
ABSTRACT Understanding sexual diversity in the social and educational context presents itself as one of the challenges for scholars in the human fields, especially in education. Based on the perception that sexual diversity is present in school life, we aim to investigate sexual diversity in a school in Brasilândia, MS, based on the memory and biography of a transsexual teacher, Jhenifer Ragnaroni. Analyzing the memory and the personal / professional life trajectory of this teacher contributes to the analysis of the displacement of the gaze on conventional (traditional) pedagogical practices, expanding the dialogues about sexuality at school. I used oral history as a research method, anchoring us in the biographical approach, with an emphasis on the teacher's memory and narratives, which makes it possible to establish relationships between the influences suffered during her life and training. In the research process, we analyzed the trajectory of Professor Jhenifer with the narratives that pervade childhood, family, and work, punctuating the conceptions of sexuality and gender experienced in the insertion path in schools. The work uses data collected through interviews with subjective and open questions and personal notes of the researched subject - memory notebook. When studying his life history, I inevitably appreciate his contribution to the formation of new modes of intervention and practice in school daily life in relation to sexuality, capable of combating prejudice and promoting equality. The biography composes the main elements for the analysis, aiming to understand the experiences lived by the other, contributing, for the research, in a significant way to the studies focused on sexuality in education. Keywords: Education. Transsexuality. Sexual diversity. Sexuality. Gender.